Coat Color Roan Shows Association with KIT Variants and No Evidence of Lethality in Icelandic Horses - Voß, Katharina (Genes (Basel), 2020)
Roan (Rn) horses show a typical seasonal change of color. Their body is covered with colored and white hair. We performed a descriptive statistical analysis of breeding records of Icelandic horses to challenge the hypothesis of roan being lethal in utero under homozygous condition. The roan to non-roan ratio of foals from roan × roan matings revealed homozygous roan Icelandic horses to be viable. Even though roan is known to be inherited in a dominant mode and epistatic to other coat colors, the causative mutation is still unknown. Nevertheless, an association between roan phenotype and the KIT gene was shown for different horse breeds. In the present study, we identified KIT variants by Sanger sequencing, and show that KIT is also associated with roan in the Icelandic horse breed.